Mutual Fund Performance in an Emerging Market: Evidence for Vietnam - Dinh, Khanh Duy (2018)
The performance of mutual funds is often measured by comparing the excess return of an active management with the returns of one or many benchmarks representing stock return characteristics. In this study, we examine three aspects of mutual fund performance, including performance in stock selection, market timing abilities of fund managers and persistence in fund returns as well. Using a sample of 103 actively managed mutual funds which focus on Vietnamese equity portfolio from 2009 to 2017, we find evidence that neither stock selection nor market timing abilities are exhibited in fund returns and thus on average the mutual funds could not outperform the overall market. Regarding the persistence in mutual fund returns, we can only obtain evidence of the "icy hands" phenomenon in portfolios of last-year loser funds. For last year winner portfolios, there is no persistence in their performance so a strategy of buying good performers of the last-year is not favorable for those return-chasing investors.